Management of Pests and Coconut (Cocos nucifera) Products in Northen Sumatra - Siregar, Ameilia Zuliyanti; Sukeksi, Lilis; Jumirah, Jumirah; Tanjung, Masitah (Jurnal Ilmu Pertanian Indonesia, 2025)
The coconut plant (Cocos nucifera L.) plays an important role in the production of cooking oil. In 2021, the area of coconut plantations in North Sumatra was 442,072.76 hectares, while the area planted in Tanjung Balai was 3,470.50 ha, with a total yield of 3755 tons. This study look at the cultivation and management of pests and coconut plant products in Tanjung Balai, North Sumatra. There were three types of coconuts found in Sei Kepayang, Tanjung Balai: tall, java, and dwarf coconut. Of the 22 coconut trees seen, 18 (81.81%) were affected by pests and diseases, including B. longissima, Orytes rhinoceros, Fusarium sp. shoot wilt disease, Curvularia sp. leaf spot disease, Pestalotiopsis palmarum gray spot disease, and monkeys and squirrels on the plants. Coconuts have a significant impact on coconut productivity. The products included cooking oil, as well as charcoal, broomsticks, rice-cake wrapp, and weaved handicrafts. Keywords: coconut, coconut pests, coconut products